Harnessing the Role of Carbon Black: A New Frontier for Energy-Density Supercapacitor Electrodes - Komariyah, Ana Yuli; Luthfiyah, Ishmah; Albadi’ah, Ida Vaeruza; Nasikhudin, Nasikhudin; Meevasana, Worawat; Diantoro, Markus (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
The performance of activated carbon (AC)-based supercapacitor electrodes is often limited by poor electrical conductivity, prompting interest in conductive additives such as carbon black (CB). This study explores the transformative potential of CB as a conductive additive in AC-based supercapacitor electrodes and systematically investigates CB mass loadings of 0%, 5%, 10%, 15%, and 20%, using styrene-butadiene rubber (SBR) as the binder. The findings in this study demonstrate that 10% CB is the optimal loading, offering a balanced performance in terms of structure, morphology, and capacitance. X-ray diffraction (XRD) analysis reveals a distinct structural evolution at 10% CB, characterized by the exclusive emergence of a (100) peak at 43° 2θ, which indicates the formation of dense graphene-like layers and enhanced π-π electron delocalization. This promotes the formation of robust conductive networks, reducing electrode resistivity by 72%. Morphological and specific surface area characterization confirms the uniform particle distribution of an ultra-thin electrode AC-10% CB (26.5 μm) with a high surface area of 851.84 m²/g; this maximizes ion-accessible active sites and minimizes diffusion pathways. These combined effects result in a specific capacitance of 61.33 F/g, representing a 12% improvement over the pristine electrode (56.36 F/g) and 89.87% capacitance retention after 50 cycles. These results highlight the importance of optimizing CB loading: Lower concentrations (